Vacuum-assisted closure in the treatment of biliary leakage following gunshot injury to the liver - Arife Şimşek,; Mahmut Burak Kılcı,; Ertuğrul Karabulut,; Müfit Sansal,; Bülent Ünal, (Turkish Journal of Gastroenterology, 2019)
Cite this article as: Şimşek A, Kılcı MB, Karabulut E, Sansal M, Ünal B. Vacuum-assisted closure in the treatment of biliary leakage following gunshot injury to the liver.  Turk J Gastroenterol 2019; 30(7): 658-9.